PELAYANAN RAWAT JALAN DI PUSKESMAS SIMPANG TIGA PEKANBARU - Sinta Dwiretno Purwanti; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The health center is the institution of health services that hold individual health services in plenary that provides out patient services, in patient, and emergency. As the public community health center is expected to provide quality health services to the public. The importance of a services the latest in any agencies have to give priority to the quality of treatment it self both in the private and government. The importance of quality services taht own many carrying an impact with good services agencies in agencies can advance it self and the achievement of the quality of services it self. The main task is to provide health services treatment, care, and health services. In providing health services, health earn income from services and facilites given.This research analyzing about the quality of services to community health centers Simpang Tiga Pekanbaru. The concept of the theory Parasuraman (2000:19) there are 5 indicators to see the quality of services : 1.Tangibles 2. Reability 3. Responsiveness 4. Empaty 5. Assurance. The riset descriptive analysis is use a qualitative analysis of data and fact about the whole describes out. The purpose of research is to analyze the public service on out patient services and to analyse the factors that affect the quality of public service on out patient services in health center Simpang Tiga Pekanbaru.This research and discussion be done about the quality of service analysis for health center Simpang Tiga Pekanbaru, it can be conclude thet the out patients in health center Simpang Tiga pekanbaru is considered to be have a maximum. It is seen from some indicators that has been achieved with good, although not be in service there are some drawbacks that could be the experience for the parties concerned.Keyword : Out patient services, Public services, Community Health Center